2018
DOI: 10.1007/s12144-018-9903-x
|View full text |Cite
|
Sign up to set email alerts
|

Adult roles as predictors of adult identity and identity commitment in Polish emerging adults: Psychosocial maturity as an intervening variable

Abstract: In the present study, we examined the relationships between adult identity, strength of identity commitments, and their potential determinants: number of adult social roles undertaken and psychosocial maturity. A total of 358 emerging adults aged 18 to 30 participated. Structural equation modelling analyses indicated that psychosocial maturity dimensions served as intervening variables between adult roles on the one hand and adult identity and identity commitments on the other. The results suggest that vocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…Developmental psychology has viewed transitions as being predominantly age-and stage-related and as following a broadly normative pattern (Crafter et al, 2019). The assumption is that transition to and engagement in corresponding (social) roles trigger psychological changes that are related to psychosocial maturation and thus lead to a modification of thinking, being, or feeling (Crafter et al, 2019;Piotrowski, Brzezińska, & Luyckx, 2018;Rankin & Kenyon, 2008).…”
Section: Gender-and Age-related Differences In Identity Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental psychology has viewed transitions as being predominantly age-and stage-related and as following a broadly normative pattern (Crafter et al, 2019). The assumption is that transition to and engagement in corresponding (social) roles trigger psychological changes that are related to psychosocial maturation and thus lead to a modification of thinking, being, or feeling (Crafter et al, 2019;Piotrowski, Brzezińska, & Luyckx, 2018;Rankin & Kenyon, 2008).…”
Section: Gender-and Age-related Differences In Identity Developmentmentioning
confidence: 99%
“…Previous research suggests that the experience of role transitions can influence identity development and re-examination (e.g., in terms of thinking about religion, or feeling a connection to cultural groups) in diverse domains (Fadjukoff, Kokko, & Pulkkinen, 2007;Kroger & Green, 1996;Luyckx, Schwartz, Goossens, & Pollock, 2008;Piotrowski et al, 2018;Syed, Azmitia, & Phinney, 2007). Kroger and Green (1996), for instance, showed that events pertaining to role transitions correlated with identity development and stage changes in various identity domains, also in ideological domains such as politics.…”
Section: Gender-and Age-related Differences In Identity Developmentmentioning
confidence: 99%
“…The sociocultural changes in the last decades have created conditions for the establishment of a new specific developmental stage -emerging adulthood (Arnett, 2001(Arnett, , 2004, occurring predominantly in young people continuing to study at the university (Côte, 2014). These sociocultural changes have delayed and complicated taking on adult social roles, such as a full-time job, partner, marriage, parenthood, and, on the other hand, have led to remaining financially and residentially dependent on parents for longer time, as full independence is not achieved in other life areas (Arnett, 2001;Piotrowski et al, 2018). This delay is not only characteristic for the United States and Western countries, but also for the rest of Europe, the Czech Republic (Macek et al, 2007) and Slovakia (Šprocha, 2018;Kohútová & Dědová, 2019) among others.…”
Section: Introductionmentioning
confidence: 99%
“…Obdobie vynárajúcej sa dospelosti je späté s obrovskými životnými zmenami vo viacerých oblastiach života. Predložená prehľadová štúdia venuje osobitnú pozornosť téme vynárajúcej sa dospelosti v kontexte identity (Whitbourne, Sneed, Sayer, 2009;Piotrowski, Brzezińska, Luyckx, 2018;Wood et al, 2018 a iné), štúdia verzus pracovnej oblasti (Schwartz et al, 2013;Mayselles, Keren, 2014;Kvapilová-Bartošová, Fučík, 2017), či partnerských a manželských vzťahov (Arnett, 2016;Shulman, Connolly, 2013;Lanz, Tagliabue, 2007).…”
Section: Definícia Pojmu Vynárajúca Sa Dospelosťunclassified
“…Jednotlivci postupne preberajú sociálne úlohy dospelého človeka. Hoci podľa viacerých autorov (Arnett, 2000;Roupa, 2016) mladí ľudia nepovažujú preberanie bežných dospelých pozícií (manžel, rodič) za významné pre definovanie seba ako dospelého, prevzatie dospelej úlohy napomáha vnímaniu seba samého ako viac dospelého (Piotrowski, Brzezińska, Luyckx, 2018). Identifikácia so sociálnou úlohou dospelého je kľúčová pri formovaní identity napriek tomu, že je mladými v období vynárajúcej sa dospelosti považovaná za irelevantnú.…”
Section: Identita V Období Vynárajúcej Sa Dospelostiunclassified